2017
DOI: 10.1038/srep45140
|View full text |Cite
|
Sign up to set email alerts
|

Gsα Controls Cortical Bone Quality by Regulating Osteoclast Differentiation via cAMP/PKA and β-Catenin Pathways

Abstract: Skeletal bone formation and maintenance requires coordinate functions of several cell types, including bone forming osteoblasts and bone resorbing osteoclasts. Gsα, the stimulatory subunit of heterotrimeric G proteins, activates downstream signaling through cAMP and plays important roles in skeletal development by regulating osteoblast differentiation. Here, we demonstrate that Gsα signaling also regulates osteoclast differentiation during bone modeling and remodeling. Gnas, the gene encoding Gsα, is imprinted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 55 publications
(88 reference statements)
5
48
2
Order By: Relevance
“…The GNAS gene is a complex imprinted locus that produces multiple transcripts (such as Gsa, XLAS, NESP55) through the use of alternative promoters and alternative splicing. A recent study by Ramaswamy et al (Ramaswamy et al, 2017) demonstrated that Gnas inactivation in mice negatively affects cortical bone quality and strength, with mutation of the paternal allele causing more severe effects than maternal mutations. These effects of Gsa deletion on bone maintenance were exerted through enhanced osteoclast differentiation and increased bone resorption, mediated by Gsa signaling via cAMP/PKA and WNT/b-catenin pathways (Ramaswamy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GNAS gene is a complex imprinted locus that produces multiple transcripts (such as Gsa, XLAS, NESP55) through the use of alternative promoters and alternative splicing. A recent study by Ramaswamy et al (Ramaswamy et al, 2017) demonstrated that Gnas inactivation in mice negatively affects cortical bone quality and strength, with mutation of the paternal allele causing more severe effects than maternal mutations. These effects of Gsa deletion on bone maintenance were exerted through enhanced osteoclast differentiation and increased bone resorption, mediated by Gsa signaling via cAMP/PKA and WNT/b-catenin pathways (Ramaswamy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Ramaswamy et al (Ramaswamy et al, 2017) demonstrated that Gnas inactivation in mice negatively affects cortical bone quality and strength, with mutation of the paternal allele causing more severe effects than maternal mutations. These effects of Gsa deletion on bone maintenance were exerted through enhanced osteoclast differentiation and increased bone resorption, mediated by Gsa signaling via cAMP/PKA and WNT/b-catenin pathways (Ramaswamy et al, 2017). SMYD3 encodes a histone methyltransferase that functions in RNA polymerase II complexes by an interaction with a specific RNA helicase (Hamamoto et al, 2004) and controls a WNT-responsive epigenetic switch (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…cAMP activation and phosphorylation of CREB in osteoblasts play important roles in skeletal development by regulating osteoblast differentiation . Additionally, CREB, acting as a potent trans‐activating factor, promotes gene transcription although p‐CREB binding to the promoter regions of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…In additional to osteoblasts and osteogenesis, cAMP/PKA signaling has also been shown to regulate osteoclastogenesis, and other pathways such as Wnt/β-catenin and calmodulin-dependent kinase have been shown to act as upstream regulators of this process[9,10]. Using a mouse model with heterozygous germline inactivation of Gsα, we demonstrated that Gsα maintains bone quality by regulating osteoclast differentiation and bone resorption activity [11]. However, given that the mouse model used globally reduced Gsα expression, we could not distinguish the contributions of a cell-autonomous role of Gsα in osteoclasts versus additional cell types.…”
Section: Introductionmentioning
confidence: 99%